Two-parton scattering in the high-energy limit: climbing two- and three-Reggeon ladders - G. Falcioni, E. Gardi, N. Maher, C. Milloy, L. Vernazza (SciPost Physics Proceedings, 2022)
We review recent progress on the calculation of scattering amplitudes in the high-energy limit. We start by illustrating the shockwave formalism, which allows one to calculate amplitudes as iterated solutions of rapidity evolution equations. We then focus on our recent results regarding 2 -> 2 parton scattering. We present the calculation of the imaginary part of the amplitude, at next-to-leading logarithmic accuracy in the high-energy logarithms, formally to all orders, and in practice to 13 loops. We then discuss the computation of the real part of the amplitude at next-to-next-to-leading logarithmic accuracy and through four loops. Both computations are carried in full colour, and provide new insight into the analytic structure of scattering amplitudes and their infrared singularity structure.